(untitled) (La Rivada, 2025)
This study investigates the experiences of many women in rural communities in eastern Yucatán, including three mothers, regarding their own educational trajectories, and how these experiences influence the continuation of their daughters’ schooling. The aimof this article is to describe the cases of three mothers from three different rural communities regarding access to education, the continuity of their daughters’ studies, and their future employment prospects. Semi-structured interviews were conducted with the participants, and their contributions were analysed using a parallel narratives approach. Findings suggest that, based on their own educational experiences, these mothers have been able to identify complex gender-related challenges and have chosen to address them on their own initiative in order to improve their daughter’s quality of life and development. They have a favorable view of the continuation of their daughters’ Education as a pathway to personal advancement, autonomy and better employment opportunities.